Ecology of Spotted Flapshell Turtle, Lissemys punctata (Lacepede, 1788) in Bangladesh - Hossain, Md. Lokman; Sarker, Shorab Uddin; Sarker, Noor Jahan (Ecoprint: An International Journal of Ecology, 2009)
Spotted flapshell turtle, Lissemys punctata was found in all types of habitats of Bangladesh. Of the 9 categories of habitats studied, the highest number (17.42%) of the turtle species was found in marshland followed by puddles (17.26%), agriculture fields (17.12%), streams (12.1%), canals (10.54%), tanks (10.39%), derelict ponds (9.18%) and domestic ponds (6.08%). Most of the time the turtle was found in burrowing condition (55.83%), rarely it was observed in feeding (7.2%) condition. The turtle seem to have a considerably higher tolerant in all types of environment, so it may be possible to set-up turtle farm commercially in Bangladesh. Key words: Spotted flapshell turtle, ecology, habitat preference, behavioral patterns. doi: 10.3126/eco.v15i0.1943 ECOPRINT 15: 59-67, 2008